Pengaruh Penerapan Kurikulum Merdeka dalam Pembelajaran Terhadap Hasil Belajar Ekonomi Siswa Kelas X Di SMA Al-Huda Pekanbaru - Wati, Indah; Mardiah, Ainul (Universitas Batanghari Jambi, 2024)
This study aims to examine the effect of implementing the Merdeka Curriculum in learning on the economics learning outcomes of tenth-grade students at Al-Huda Senior High School in Pekanbaru. This research used a quantitative approach with quantitative descriptive analysis techniques. The population of the study consisted of all tenth-grade students at Al-Huda Senior High School in Pekanbaru, totaling 61 students, selected through total sampling techniques. Data collection was carried out through documentation and questionnaires. The research results showed that the implementation of the Merdeka Curriculum had an impact on the economics learning outcomes of students at Al-Huda Senior High School in Pekanbaru. Based on the findings, the implementation of the Merdeka Curriculum scored 78.01%, categorized as good, while the average score of students' economics learning outcomes was 78.25, categorized as sufficient. The correlation coefficient analysis indicated that the t-observed value was higher than the t-table value (5.278 > 1.67), which signifies a significant effect of the Merdeka Curriculum implementation on economics learning outcomes. The R Square value of 0.321 shows that 32.1% of the learning outcomes were influenced by the curriculum implementation, while the remaining 67.9% was influenced by other variables.